Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Determining the subjective and physiological effects of BZP combined with TFMPP in human males - Joanne C. Lin; Reem K. Jan; HeeSeung Lee; Maree-Ann Jensen; Rob R. Kydd; Bruce R. Russell (Psychopharmacology, 2011)

Influence of indomethacin on the ventilatory and cerebrovascular responsiveness to hypoxia - Jui-Lin Fan; Keith R. Burgess; Kate N. Thomas; Karen C. Peebles; Samuel J. E. Lucas; Rebekah A. I. Lucas; James D. Cotter; Philip N. Ainslie (European Journal of Applied Physiology, 2011)

The controlled in vitro susceptibility of gastrointestinal pathogens to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

Global patterns in the biogeography of bacterial taxa - Diana R. Nemergut; Elizabeth K. Costello; Micah Hamady; Catherine Lozupone; Lin Jiang; Steven K. Schmidt; Noah Fierer; Alan R. Townsend; Cory C. Cleveland; Lee Stanish; Rob Knight (Environmental Microbiology, 2011)
Summary Bacteria control major nutrient cycles and directly influence plant, animal and human health. However, we know relatively little about the forces shaping their large‐scale ecological ranges. Here, we reveal patterns in the distribution of individual bacterial taxa at multiple levels of phylogenetic resolution within and between Earth's major habitat types. Our analyses suggest that while macro‐scale habitats structure bacterial distribution to some degree, abundant bacteria (i.e. detectable using 16S rRNA gene sequencing methods) are confined to single assemblages. Additionally, we show that the most cosmopolitan taxa are also the most abundant in individual assemblages. These results add to the growing body of data that support that the diversity of the overall bacterial metagenome is tremendous. The mechanisms governing microbial distribution remain poorly understood, but our analyses provide a framework with which to test the importance of macro‐ecological environmental gradients, relative abundance, neutral processes and the ecological strategies of individual taxa in structuring microbial communities.